The Evolution of the Canadian Pension Model : Practical Lessons for Building World-Class Pension Organizations - World Bank Group (World Bank, Washington, DC, 2017)
Canada is home to some of the world's most admired and successful public pension organizations. This was not always the case. As recently as the mid-1980s, many Canadian public pensions were invested largely or entirely in domestic government bonds, were funded primarily on a pay-as-you go basis, lacked independent governance, and were administered in an outdated and error-prone fashion. Over the past three decades, a Canadian model of public pension has emerged that combines independent governance, professional in-house investment management, scale, and extensive geographic and asset-class diversification. This report aims to document the emergence and evolution of this Canadian model, distilling practical lessons for stakeholders in emerging economies working to improve their pension arrangements and retirement systems. Although a growing body of literature exists on the Canadian model of pension organization, this report is unique in two respects: its emphasis on the evolutionary journey of Canadian pension organizations (as opposed to their current state) and its in-depth focus on Canadian pension funds that have received less attention than some of their peers.